Mid Term Appraisal for Tenth Five Year Plan (2002-2007) Government of Manipur - Planning Commission (Planning Commission, 2004)
The Tenth Five Year Plan (2002-2007) of Manipur was prepared against the backdrop of high expectations of achieving the targeted growth rate of 6.5% and also in the context of national priorities and objectives while considering its unique socioeconomic issues and prospects and potentials. Since the preparation of Tenth Plan proposals, the State has been facing multifarious problems in terms of wide disparity in the level of development, inadequate allocation of funds in the past plans period, weak resource position, inter districts disparity, high rate of unemployment, underdevelopment and more importantly the law and order problem. As per the Index of Relative Development of Infrastructure/report prepared by different agencies such as the Centre for Monitoring of Indian Economy, the Planning Commission as well as Eleven Finance Commission, Manipur occupies a low place in the list. the level of development in infrastructure such as roads, power, irrigation, etc. lags behind other states of the country.
Planning Department, Government of Manipur